Lingering effects of foreign resource dependency in Pakistan: Assessing gains from domestic resources - Mubbasher Munir; Muhammad Saeed Meo; Kinza Younas; Noman Arshed; Asma Khalid Jamil (Universitas Islam Indonesia, 2021)
Purpose - This study explores the asymmetric effects of FDI (Foreign Direct Investment) on economic growth in Pakistan.Methods - This paper uses an Asymmetric Effects ARDL (Autoregressive Distributed Lag) model.Findings - The results show that the effects of increasing and decreasing FDI are not equal. The study concludes that reducing FDI is more beneficial for economic growth, particularly in the longer horizon. It mobilizes domestic investment and promotes financial freedom while reducing the reliance on pollution-intensive multinational corporations and taps indigenous knowledge gains.Implications - This study proves that self-reliance is more beneficial for the case of Pakistan.Originality - The researchers and policymakers are unclear about the merits and demerits of FDI as a substitute for domestic investment. Empirical studies are majorly convinced that an increase in FDI generally merits economic growth but weighs in the Pollution Haven Hypothesis and ignores the indigenous knowledge-based domestic resource.